2020
DOI: 10.1002/cmdc.202000339
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Specific Iodine‐125‐Labeled TRPC5 Radioligand

Abstract: The nonselective Ca 2 +-permeable transient receptor potential channel subfamily member 5 (TRPC5) belongs to the transient receptor potential canonical (TRPC) superfamily and is widely expressed in the brain. Compelling evidence reveals that TRPC5 plays crucial roles in depression and other psychiatric disorders. To develop a TRPC5 radioligand, following up on our previous effort, we synthesized the iodine compound TZ66127 and its iodine-125-labeled counterpart [ 125 I]TZ66127. The synthesis of TZ66127 was ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Bauer et al used a competitive photoaffinity labelling approach to demonstrate that the effect of xanthines such as Pico145 on TRPC5 channels is mediated by a direct binding interaction (65), and subsequent cryo-EM studies revealed the TRPC5 binding site and mode of Pico145 (see below) (66). In addition, Yu et al reported the development of a Pico145-based 11 C and 125 I radiotracers (67,68). Just et al reported the anxiolytic and antidepressant effects in mice of a close analogue of Pico145, named HC-070 (64).…”
Section: Trpc1/4/5 Channel Inhibitorsmentioning
confidence: 99%
“…Bauer et al used a competitive photoaffinity labelling approach to demonstrate that the effect of xanthines such as Pico145 on TRPC5 channels is mediated by a direct binding interaction (65), and subsequent cryo-EM studies revealed the TRPC5 binding site and mode of Pico145 (see below) (66). In addition, Yu et al reported the development of a Pico145-based 11 C and 125 I radiotracers (67,68). Just et al reported the anxiolytic and antidepressant effects in mice of a close analogue of Pico145, named HC-070 (64).…”
Section: Trpc1/4/5 Channel Inhibitorsmentioning
confidence: 99%